Pyrimidine salvage in Toxoplasma gondii as a target for new treatment - Elati, Hamza A. A.; Goerner, Amber L.; Martorelli Di Genova, Bruno; Sheiner, Lilach; de Koning, Harry P. (Frontiers in Cellular and Infection Microbiology, 2023)
Toxoplasmosis is a common protozoan infection that can have severe outcomes in the immunocompromised and during pregnancy, but treatment options are limited. Recently, nucleotide metabolism has received much attention as a target for new antiprotozoal agents and here we focus on pyrimidine salvage by Toxoplasma gondii as a drug target. Whereas uptake of [3H]-cytidine and particularly [3H]-thymidine was at most marginal, [3H]-uracil and [3H]-uridine were readily taken up. Kinetic analysis of uridine uptake was consistent with a single transporter with a Km of 3.3 ± 0.8 µM, which was inhibited by uracil with high affinity (Ki = 1.15 ± 0.07 µM) but not by thymidine or 5-methyluridine, showing that the 5-Me group is incompatible with uptake by T. gondii. Conversely, [3H]-uracil transport displayed a Km of 2.05 ± 0.40 µM, not significantly different from the uracil Ki on uridine transport, and was inhibited by uridine with a Ki of 2.44 ± 0.59 µM, also not significantly different from the experimental uridine Km. The reciprocal, complete inhibition, displaying Hill slopes of approximately -1, strongly suggest that uridine and uracil share a single transporter with similarly high affinity for both, and we designate it uridine/uracil transporter 1 (TgUUT1). While TgUUT1 excludes 5-methyl substitutions, the smaller 5F substitution was tolerated, as 5F-uracil inhibited uptake of [3H]-uracil with a Ki of 6.80 ± 2.12 µM (P > 0.05 compared to uracil Km). Indeed, we found that 5F-Uridine, 5F-uracil and 5F,2’-deoxyuridine were all potent antimetabolites against T. gondii with EC50 values well below that of the current first line treatment, sulfadiazine. In vivo evaluation also showed that 5F-uracil and 5F,2’-deoxyuridine were similarly effective as sulfadiazine against acute toxoplasmosis. Our preliminary conclusion is that TgUUT1 mediates potential new anti-toxoplasmosis drugs with activity superior to the current treatment.